The birds of the islands of Flores - A review - J Verhoeye; Derek A Holmes (KUKILA, 1998)
The avifauna of the island of Flores and its satellite islands from Komodo to Alor is reviewed, combining historical data with recent observations. Recent surveys have added substantially to the data base, especially of the resident forest species, and endangered and endemic taxa, as well as adding a number of migrant and maritime species to the island list. Of particular interest are the rare forest endemics Wallace's Hanging parrot Loriculus floscutus, the almost unknown Flores Scops-owl Otus alfredi, Flores Monarch Monarcha sacerdotum and Flores Crow Corvus florensis. An appeal is made for further surveys over the eastern part of the island and the eastern island chain.